Capillary breakup extensional rheometry of sodium carboxymethylcellulose solutions in water and propylene glycol/water mixtures. Issue 22 (6th November 2019) - Różańska, Sylwia; Verbeke, Karel; Różański, Jacek; Clasen, Christian; Wagner, Patrycja
ABSTRACT: This article presents the results of capillary break‐up extensional rheometer experiments conducted for semidilute solutions of carboxymethylcellulose sodium salt (Na‐CMC) with degrees of substitution (DS) ranging from 0.62 to 1.04 in distilled water and propylene glycol (PG)/water mixtures. The partial aggregation of Na‐CMC chains with DS < 1 observed in aqueous solutions triggers an increase in apparent extensional viscosity and extension of break‐up time. The rheological properties of Na‐CMC solutions in propylene glycol/water mixture are determined by the solubility of the polymer and the physical crosslinking of chains. The disappearance of the elasto‐capillary regime during the filament thinning of Na‐CMC solutions with DS < 1 in propylene glycol/water mixture was linked to the physical crosslinking of polymer chains. The shape of the extensional viscosity curve for Na‐CMC solutions with DS = 1.04 in PG/water mixture was characteristic for semidilute polymer solutions with a low number of entanglements. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2019, 57, 1537–1547 Abstract : The CaBER rheometer is used to measure extensional viscosity of low‐viscosity fluids. With the use of that type of rheometer, the apparent extensional viscosity and the extensional rate can be determined using the time‐dependent changes in the fiber midpoint diameter and with performing the independent measurement of surface tension. This article presents measurement results obtained with use of a CaBER rheometer for semi‐diluted Na‐CMC solutions in water and propylene glycol/water mixtures.